STRATEGY FOR REDUCING THE NUMBER OF DIVORCES THROUGH IMPROVING LEGAL MATERIALS - Dr. Anwar Sadat, S.Ag, M.Hum; Dr. KRT. Hardi Mulyono; Dr. Dani Sintara, SH, MH; Halimatul Maryani, SH, MH (Journal of Islamic, Social, Economics and Development, 2023)
There have been many laws and regulations that have been used as a reference in the implementation of marriages in Indonesia, including as guidelines in the divorce process, in fact they have not been able to stem the number of divorces in society, in fact the number has continued to increase from year to year. Under these conditions, it means that there are some deficiencies in the law on marriage that need to be perfected, so that husband and wife are not arbitrary and easy to divorce. Because even though divorce is permissible, the implementation process must be carried out selectively and with great care, so that the impact of losses and harm that may arise in the future can be minimized. After conducting in-depth analysis and research on laws and regulations related to marriage, it turns out that there are 2 (two) main issues that need to be urgently refined, so that people do not easily and haphazardly file for divorce. The two main issues that are being refined are meant, namely: 1) improvement of material on marriage legislation relating to the reasons that are permissible and not permissible in carrying out a divorce, 2) improvement of material on marriage legislation relating to the criteria for determining a mediator (hakam) in resolve marital disputes or divorce proceedings.